AMPA Receptor Binding Cleft Mutations That Alter Affinity, Efficacy, and Recovery from Desensitization - Robert, Antoine (J Neurosci, 2005)
Glutamate binds to AMPA receptors within a deep cleft between two globular protein domains (domains 1 and 2). Once glutamate binds, the cleft closes, and agonist-bound structures of the isolated ligand binding core suggest that closure of the binding cleft is sufficiently complete that it essentially prevents ligand dissociation. There is also considerable evidence supporting the view that cleft closure is the initial conformational change that triggers receptor activation and desensitization, and it has been clearly demonstrated that there is a correlation between the degree of cleft closure and agonist efficacy. It is unknown, however, whether the stability of binding cleft closure also influences receptor-channel properties. The crystallographic structures indicate that closed-cleft conformations are stabilized by the formation of hydrogen bonds that involve amino acid side chains of residues in domains 1 and 2. We show here that mutations that disrupt one such cross-cleft hydrogen bond (in the AMPA receptor subunit GluR2) decrease both agonist affinity and efficacy. The same mutations also hasten recovery from desensitization. We conclude that the stability of binding cleft closure has a significant impact on AMPA receptor function and is a major determinant of the apparent affinity of agonists. The results suggest that the stability of cleft closure has been tuned so that glutamate dissociates as rapidly as possible yet remains a full agonist.